İbn Kalanisî, hayatı ve eserleri “Zeylü Tarihî Dımaşk” tercümesi (S.142-549) - Aydın, Hasan (My University, 2016)
Bu çalışmada H.450(1059)-555(1160) yılları arasında Bilâdü’ş-Şâm ve el-Cezîre bölgesindeki olaylara ışık tutan İbnü’l-Kalânisî’nin Zeylü Tarihi Dımaşk adlı eseri, müellifin takip ettiği yıllık usulü üzere Arapçasından tercüme edilmiştir. Metinde geçmekte olan ve bugün ismi değişmiş yahut coğrafî olarak bilinmeyen yerlerin isimleri, coğrafî konumları dönemin kaynaklarıyla mukayese edilerek açıklanmış devlet kurumlarına ait ıstılahlar izah edilmiştir. Müellifin naklettiği tarihî olaylar muasır ve muahhar diğer tarihi kaynaklarla karşılaştırılarak hadise ve tarihî kişiliklerin sağlaması yapılmıştır. Kalânisî, Bilâdü’ş-Şâm, Dımaşk, el-Cezîre, Selçuklular, Börîler, Zahireddin Atabek, Zengîler, Haçlı Seferleri, Fâtımî Halifeliği, Abbâsî Halifeliği

In this study, İbn al-Qalanisî’s work called the Dhail al-Tarîkh al-Dimashq which sheds light on the events in the Bilad al-Sham and al-Jazeera region between the years 450 A.H. (1059) – 555 A.H. (1160), has been translated from Arabic into Turkish according to the annual procedure followed by the author. The place names are mentioned in the text are changed today or are not geographically known, have been explained by comparing their geographical locations with that period’s sources; technical terms of the state institutions have been explained. The events and the historical people have been crosschecked with the comparison of historical events which the author has conveyed, with other contemporaneous and subsequent historical events Qalanisî, Bilad al-Sham, Damascus, al-Jazeera, Seljuks, Borids, Zahir al-Din Atabeg, Zengids, the Crusades, the Fatimid Caliphate, the Abbasid Caliphate
Keywords: Şam (Suriye); Tarih